MiR-27a regulates Wnt/beta-catenin signaling through targeting SFRP1 in glioma. Issue 12 (19th August 2015) - Wang, Kun; Xie, Dajiang; Xie, Jixi; Wan, Yingfeng; Ma, Li; Qi, Xuchen; Yang, Shuxu
Abstract : Glioma is one of the most common intracranial tumors, and the prognosis is poor, although more and more treatments are employed. Wnt/beta-catenin signaling has been reported to be associated with glioma. SFRP1 acts as an antagonist and inhibits Wnt signaling by binding to Wnt molecules. In the present study, we aimed to investigate miRNA-27a as an antineoplastic factor that inhibits the Wnt/beta-catenin pathway by binding to the SFRP1 3′-UTR in glioma in vitro . We first showed that the expression of miR-27a was elevated in both glioma samples and cell lines. Furthermore, downregulation of miR-27a induced growth inhibition, cycle arrest, and apoptosis, and suppressed invasion/migration in glioma cell lines. Quantitative real-time PCR, western blot, and luciferase assay analysis showed that SFRP1 is a direct target of miR-27a. Overexpression of SFRP1 inhibited the malignancy of glioma cell lines. Our investigation showed that downregulation of miR-27a suppressed beta-catenin/TCF-4 transcription activity by targeting SFRP1. Our findings identify a role for miR-27a in glioma cell viability, cycle, apoptosis, and invasion/migration after activation of Wnt/beta-catenin signaling through SFRP1.